2022
DOI: 10.21315/mjms2022.29.1.6
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Cutting Seton for High Transsphincteric Anal Fistula in the Era of Its Misery

Abstract: Objectives: We studied the outcome of cutting seton in the treatment of a high transsphincteric anal fistula in Sudan. Methods: This was a prospective study of high transsphincteric anal fistulas at Kassala Police Hospital, Sudan, over the course of 24 months (2016–2017). The main outcomes measured were recurrence, incontinence and primary healing rates. Results: The cases of 72 patients treated with cutting seton for high transsphincteric fistula were analysed, with 50 (70%) of the patients being male and 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Остальные 7 (9,7 %) пациентов выздоровели позже 60 дней. О хронической боли сообщили 2 (2,8 %) человека после полного заживления [66].…”
Section: хирургическое лечениеunclassified
“…Остальные 7 (9,7 %) пациентов выздоровели позже 60 дней. О хронической боли сообщили 2 (2,8 %) человека после полного заживления [66].…”
Section: хирургическое лечениеunclassified
“…Fistulectomy, a common surgical technique for high anal fistulas, involves complete exposure and excision of the tract, branches, and abscess cavity, followed by adequate drainage, effectively removing necrotic tissue and eliminating recurrence factors. However, this approach can lead to significant postoperative pain, slow wound healing, severe anal deformity, incontinence, and other complications 10,11 . The seton technique, a traditional Chinese medical treatment, employs a thread or rubber band's constrictive force to slowly cut through the muscle encompassed by the fistula tract, thus preserving the anatomical and physiological functions of the anus 12 .…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach can lead to significant postoperative pain, slow wound healing, severe anal deformity, incontinence, and other complications. 10 , 11 The seton technique, a traditional Chinese medical treatment, employs a thread or rubber band's constrictive force to slowly cut through the muscle encompassed by the fistula tract, thus preserving the anatomical and physiological functions of the anus. 12 Some studies have shown that, compared to simple cutting seton surgery, loose combined cutting seton surgery can effectively improve postoperative drainage and alleviate pain in patients with high anal fistulas.…”
Section: Introductionmentioning
confidence: 99%
“…Fistula-in-ano, or anal fistula, is a painful and persistent ailment that frequently presents medical experts with difficulties due to its recurrence and post-operative problems [1]. Traditional treatments include fistulotomy or seton procedures, but these cases show how the Kshara Sutra can be applied and surgical strategies can be effective in managing the condition [2]. Anal fistulas are a chronic, difficult-to-treat condition that frequently leaves patients in great agony and presents a huge challenge to medical experts [3].…”
Section: Introductionmentioning
confidence: 99%